Project anticipation as a tool for built environment social resilience - Fanzini, Daniele; Rotaru, Irina (TECHNE - Journal of Technology for Architecture and Environment, 2018)
The researches of Adger (2000), Martini (2015) and Malcevschi et al. (2017) suggest that there is an indissoluble relationship between society, territory and economy, factors which have reciprocal influence on each other in the creation of a specific ecosystem. The connection between these three elements feeds the built environment processes, predisposing its life cycle to various types of resilience. By analysing certain case studies, this paper aims to illustrate various forms of social resilience comforted by the anticipatory approach. The solutions proposed are presented together with details of the process models adopted and subsequently linked to different project and management methodologies which can be connected to the specifics of the technological project.